Teacher Stroke as a Positive Interpersonal Behavior on English as a Foreign Language Learners' Success and Enthusiasm - Song, Zhe (Frontiers in Psychology, 2021)
In the context of language learning, teacher-student interactions are regarded as pivotal for their impact on the education of learners and their academic journey. To help learners succeed, the teachers may employ various ways to develop this interpersonal relationship, one of which is teacher stroke which is also called teacher praise. Interpersonal skills, societal encouragement, and stroking manners, respect, consideration, or reactions that an individual provides for others can uphold such a connection and can affect the enthusiasm of the students. To this end, this study makes an effort to review the prominence of teacher stroke in the process of learning in the classroom and illustrate their relationship and their impact on the enthusiasm and success of the learners. Furthermore, this study contributes to the body of dominant literature and suggestions and recommendations have been presented for the language teaching stakeholders in the educational setting.